PROFESSIONAL PECULIARITIES OF A SPECIAL TEACHER OF A GENERAL EDUCATIONAL SCHOOL - Кошжанова, Гульшат; Шырынбаева, Гүлбахира; Қазақбаева, Гүлнұр; Қалықова, Алмагүл (Pedagogy and Psychology, 2023)
The article highlights the professional features of a special pedagogical specialist in the system of general education. Currently, a number of educational institutions create special conditions on their basis, allowing children with disabilities to offer changing forms of education in accordance with their characteristics and the needs of society in educational services. Parents (legal representatives) are given the right to choose an affordable educational institution at the place of residence, the form of education. Inclusive experience and integrated learning are widely used to successfully acquire cultural experience, taking into account age characteristics, internal resources, health status and individual capabilities of each child. The content of the activity of a teacher-defectologist is implemented in the following areas of work, providing an integrated approach to its organization: diagnostic, corrective, analytical, consultative and educational and preventive, organizational and methodological. In addition to the traditional areas of work, an analytical application was identified that determines the interaction of specialists in work, and also allows you to adjust curricula in accordance with the achievements of students.